Speaking COVID-19: supporting COVID-19 communication and engagement efforts with people from culturally and linguistically diverse communities - Holly Seale; Ben Harris-Roxas; Anita Heywood; Ikram Abdi; Abela Mahimbo; Ashfaq Chauhan; Lisa Woodland (BMC, 2022)
Abstract Background Since the emergence of COVID-19, issues have been raised regarding the approach used to engage with Culturally and Linguistically Diverse (CaLD) communities during this public health crisis. This study aimed to understand the factors impacting communication and engagement efforts during the COVID-19 pandemic from the perspective of crucial CaLD community stakeholders and opinion leaders. Methods Forty-six semi-structured telephone interviews were undertaken with key stakeholders who have an active role (established before the pandemic) in delivering services and other social support to CaLD communities in Australia. Results Seven key themes emerged: (1) the digital divide and how to connect with people; (2) information voids being filled by international material; (3) Differentiating established with new and emerging communities' needs; (4) speaking COVID-19; (5) ineffectiveness of direct translations of English language resources; (6) coordination is needed to avoid duplication and address gaps and (7) recognising the improvements in governments' approach. Conclusion Alliances must be set up that can be activated in the future to reduce issues around resource development, translation, and dissemination of messages to minimise gaps in the response. Financial assistance must be provided in a timely way to community organisations to support the development and dissemination of culturally appropriate communication materials.